Country Girls Fight, Too: The Relationship Between Social Support and Rural Female Youth Violence - Malone, Redhonda Vanessa (2018)
This study was conducted to explore the relationship between social support and youth violence by testing the relationships between violence victimization, violence exposure, violence perpetration, delinquency, and the moderating variable of social support for rural female adolescents in the United States. This research, guided by the social disorganization theory, involved analyses of data from Wave 3 of the National Survey for Children's Exposure to Violence. The logistic regression analyses (n = 278; female; rural area; mean age 13.5) showed no moderating effect of social support on youth violence perpetration. However, there was a positive association between delinquency and violence perpetration, and a relationship between violence victimization in the forms of child maltreatment, exposure to peer victimization, exposure to sibling victimization, exposure to family violence, witnessing violence, and indirect victimization and violence perpetration. The research contributes to positive social change by providing more evidence about the gender-specific needs of rural adolescent females. This evidence may be used in the development of sustainable violence prevention programs and other services designed to prevent child maltreatment and other forms of violence exposure and victimizations, and subsequent violence perpetration